Emergency conservation interventions during times of crisis: A case study for a threatened bird species in the Australian Black Summer bushfires. Issue 2 (24th December 2021) - Selwood, Katherine E.; Antos, Mark; Bramwell, Mick; Lee, Adam; Lynch, Michael; Magrath, Michael J. L.; Maute, Kimberly; Melvin, Fiona; Mott, Rowan; Perri, Marc; Whiteford, Craig; Clarke, Rohan H.
Abstract: Emergency conservation interventions will be increasingly necessary to prevent extinctions or severe population bottlenecks as extreme events become more frequent. We detail the emergency extraction of the endangered Eastern Bristlebird ( Dasyornis brachpterus ) during the unprecedented 2019–2020 Australian Black Summer bushfires, an intervention that led to the rapid establishment of a temporary ex situ insurance population sourced from an area under immediate threat from bushfire (Croajingolong National Park, Victoria). The intervention was triggered, coordinated, and implemented within a 4‐week period, with re‐release to the wild within 2 months. We present this case study within a framework for emergency conservation interventions, based on the emergency management phases of preparation, response, and recovery, with the addition of an evaluation phase. The preparation phase involved compiling existing knowledge and capacity to facilitate the operation. The response phase consisted of (a) initiation and planning of the intervention (coordination) and (b) implementation, that is, the translocation of 15 birds from an area under threat of bushfire to a captive institution (>500 km). The recovery phase saw the insurance population re‐released to unburnt habitat after the bushfire had ceased. The evaluation phase incorporated lessons learnt from the other three phases as part of an adaptive management approach. We reflect on the Eastern Bristlebird emergency conservation intervention to explore how we can better prepare for, respond to, and recover from the large range of emergencies faced by biodiversity around the world. Abstract : An emergency conservation intervention was implemented for the endangered Eastern Bristlebird during the Australian Black Summer bushfires to establish a temporary ex situ insurance population sourced from an area under immediate threat of bushfire. We document lessons learnt from our case study, under a framework for emergency conservation interventions based on the phases of preparation, response, recovery, and evaluation.